Titanium product surface long-acting stable antibacterial coating and preparation method thereof

Gradient copper element nanotubes were prepared by pretreatment, anodizing and hydrothermal reaction of titanium products, which solved the problems of short duration of antibacterial effect of titanium products and unstable release of metal particles, and achieved long-term and stable antibacterial effect on the surface of titanium products.

CN119553334APending Publication Date: 2025-03-04XIAN UNIV OF TECH

Patent Information

Application Number
CN202411567953.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The antibacterial effect of existing titanium products is short and the release of metal particles is unstable, so it cannot achieve long-term and stable antibacterial effect.

Method used

Gradient copper element nanotubes were prepared by pretreatment of titanium products, two anodizations and four hydrothermal reactions, and a long-term stable antibacterial coating on the surface of titanium products.

Benefits of technology

The long-term and stable antibacterial effect on the surface of titanium products and the stable release of copper elements have been achieved, solving the problems of the short duration of the antibacterial effect of existing antibacterial metal-doped titanium alloys and the unstable release of metal particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553334A_ABST
    Figure CN119553334A_ABST
Patent Text Reader

Abstract

The invention discloses a long-acting stable antibacterial coating on the surface of a titanium product and a preparation method. The preparation method specifically comprises the following steps: pre-treating the titanium product; then, the titanium product is subjected to anodic oxidation twice, ultrasonic cleaning and drying, and a titanium dioxide nanotube pre-implanted with the copper element is prepared; and performing hydrothermal reaction on the titanium dioxide nanotube pre-implanted with the copper element for four times, cleaning and drying to obtain the long-acting stable antibacterial coating on the surface of the titanium product. According to the method, the gradient copper element nanotube is prepared through anodic oxidation of the pre-implanted copper element and four hydrothermal reactions, the coating of a gradient structure in which the content of the copper element is gradually increased from the interior of the nanotube to the exterior is obtained, and the copper element can be stably released while the antibacterial performance of the titanium product is guaranteed; the problems that an existing antibacterial metal doped titanium alloy is short in antibacterial effect lasting time, unstable in metal particle release and poor in antibacterial property are solved, and the titanium alloy serves as a long-acting and stable antibacterial coating on the surface of a titanium product and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium product surface coating preparation, and specifically relates to a method for preparing a long-acting stable antibacterial coating on the surface of a titanium product, and also relates to the long-acting stable antibacterial coating on the surface of the titanium product. Background Art

[0002] Titanium and titanium alloys have excellent properties such as light weight, high strength, corrosion resistance, biocompatibility and excellent processing performance, and are widely used in daily life, medical equipment and other fields. And from medical equipment to daily necessities, materials with antibacterial effects can effectively reduce the risk of infection and improve public health safety. However, titanium itself does not have significant antibacterial properties, and this deficiency limits its application in these fields. Modifying the titanium surface by physical or chemical means, such as combining antibacterial agents such as silver and zinc with titanium alloys, can effectively inhibit bacterial growth and enhance the antibacterial effect of the material. However, these antibacterial agents have problems such as uneven release rate and short duration of antibacterial effect, which is not conducive to the long-term use of titanium alloys. Therefore, it is of great significance to develop titanium product surface coating materials with long-lasting and stable antibacterial effects.

[0003] A Chinese patent (application number: 202110638401.X, publication number: 115444980A, publication date: 2022-12-09) discloses a metal ion-doped titanium dioxide nanocoating, a preparation method and its application in nerve and bone tissue repair. The nanocoating uses interlaced titanium dioxide nanowires as carriers, and alkaline earth metals or transition metals are present in the form of ions or oxides on the surface of the titanium dioxide nanowires or incorporated into the titanium dioxide lattice in the form of ions, so as to be used in the repair of nerve and bone tissue. However, the antibacterial activity of the doped metal particles is poor, and the release of metal ions is unstable, so the purpose of long-term and stable antibacterial cannot be achieved. A Chinese patent (application number: 201410053950.0, publication number: 103820834A, publication date: 2014-05-28) discloses a method for preparing titanium dioxide nanotubes and doping them with silver. The titanium dioxide nanotubes are prepared by an anodic oxidation method, and nanosilver particles are doped on the titanium dioxide nanotubes by a photochemical reduction method, thereby obtaining titanium dioxide nanotubes doped with silver particles. However, the nanosilver particles will produce an explosive release in a short period of time, and the short-term antibacterial effect is excellent, but it is not conducive to long-term use.

[0004] A Chinese patent (application number: 202011171661.2, publication number: 112219867A, publication date: 2021-01-15) discloses a metal particle-enhanced titanium dioxide antibacterial composite, which combines titanium dioxide, silver ions and other organic compounds to obtain a titanium dioxide antibacterial composite with antibacterial function. However, the release rate of silver ions cannot be controlled, and the composite can only have high antibacterial activity in a short time, which is not conducive to long-term use.

[0005] A Chinese patent (application number: 202211149735.1, publication number: CN115478255A, publication date: 2022-12-16) discloses a method for preparing a silver-containing nano-composite antibacterial coating. The magnetron sputtering technology is used to deposit a titanium transition layer, a silver-doped titanium dioxide layer, a nano-silver particle layer, and a titanium dioxide layer on the surface of the substrate in sequence, which can effectively extend the antibacterial time. However, the release rate of the antibacterial agent cannot be controlled, and there are problems such as explosive release during use, which is not conducive to safe use. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product, so as to solve the problems that the antibacterial effect of existing titanium products lasts for a short time and the release of metal particles is unstable.

[0007] Another object of the present invention is to provide a long-lasting and stable antibacterial coating on the surface of titanium products.

[0008] The technical solution adopted by the present invention is a method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product, which is specifically implemented according to the following steps: Step 1, pretreatment of titanium products; Step 2, anodizing the titanium product obtained in step 1 twice, ultrasonically cleaning it with deionized water after the oxidation is completed, and drying it at room temperature to obtain titanium dioxide nanotubes pre-implanted with copper elements; Step 3, subjecting the titanium dioxide nanotubes pre-implanted with copper obtained in step 2 to four hydrothermal reactions, washing and drying, to obtain a long-lasting and stable antibacterial coating on the surface of the titanium product.

[0009] The present invention is also characterized in that: In step 1, specifically: The titanium product is polished in sequence using sandpaper from coarse to fine, and then pickled using a mixed solution to obtain a pre-treated titanium product.

[0010] The mixed solution is prepared by mixing deionized water, nitric acid and hydrofluoric acid in a volume ratio of 12.5~10:2~4:0.5~1.

[0011] In step 2, during anodization, the electrolyte is a mixture of ethylene glycol, water, ammonium fluoride, and copper chloride in a mass ratio of 96-90:2-5:1-2:1-3; the anodization voltage is 50-60V, and the time is 0.5-1h.

[0012] In step 3, the specific steps are as follows: Step 3.1, mixing the titanium dioxide nanotubes pre-implanted with copper obtained in step 2 with the primary mixed solution, and performing a first hydrothermal reaction to obtain primary copper-doped nanotubes; Step 3.2, mixing the primary copper-doped nanotubes obtained in step 3.1 with the secondary mixed solution, and performing a second hydrothermal reaction to obtain secondary copper-doped nanotubes; Step 3.3, mixing the secondary copper-doped nanotubes obtained in step 3.2 with the tertiary mixed solution, and performing a third hydrothermal reaction to obtain tertiary copper-doped nanotubes; Step 3.4, mixing the tertiary copper-doped nanotubes obtained in step 3.3 with the quaternary mixed solution, performing a fourth hydrothermal reaction to obtain quaternary copper-doped nanotubes, washing and drying, and thus obtaining a long-lasting and stable antibacterial coating on the surface of the titanium product.

[0013] The temperatures of the four hydrothermal reactions were all 200~240℃, and the reaction times were all 1~3h.

[0014] The primary mixed solution, the secondary mixed solution, the tertiary mixed solution and the quaternary mixed solution are all prepared by mixing barium hydroxide solution, copper chloride solution and sodium hydroxide solution; In the primary mixed solution, the volume ratio of the barium hydroxide solution, the copper chloride solution and the sodium hydroxide solution is 1-2:1-2:96-98; the concentration of the barium hydroxide solution is 0.01-0.03 mol / L; the concentration of the copper chloride solution is 0.005-0.02 mol / L; the concentration of the sodium hydroxide solution is 8-10 mol / L; In the secondary mixed solution, the volume ratio of the barium hydroxide solution, the copper chloride solution and the sodium hydroxide solution is 1-2:3-4:94-96; the concentration of the barium hydroxide solution is 0.01-0.03 mol / L; the concentration of the copper chloride solution is 0.03-0.05 mol / L; the concentration of the sodium hydroxide solution is 8-10 mol / L; In the three mixed solutions, the volume ratio of barium hydroxide solution, copper chloride solution and sodium hydroxide solution is 1~2:5~6:92~94; the concentration of barium hydroxide solution is 0.01~0.03mol / L; the concentration of copper chloride solution is 0.06~0.08mol / L; the concentration of sodium hydroxide solution is 8~10mol / L; In the four mixed solutions, the volume ratio of the barium hydroxide solution, the copper chloride solution and the sodium hydroxide solution is 1~2:7~8:90~92; the concentration of the barium hydroxide solution is 0.01~0.03mol / L; the concentration of the copper chloride solution is 0.1~0.12mol / L; and the concentration of the sodium hydroxide solution is 8~10mol / L.

[0015] Another technical solution adopted by the present invention is an antibacterial coating prepared by a method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product.

[0016] The beneficial effects of the present invention are: The method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product of the present invention prepares gradient copper nanotubes by pre-implanting copper elements through anodic oxidation and four hydrothermal reactions, thereby obtaining a coating with a gradient structure in which the copper content gradually increases from the inside to the outside of the nanotubes. The copper element can be stably released while ensuring the antibacterial properties of the titanium product, thereby solving the problems of short duration of antibacterial effect, unstable release of metal particles, and poor antibacterial properties of existing antibacterial metal-doped titanium alloys. The coating can be used as a long-lasting and stable antibacterial coating on the surface of titanium products, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic diagram of the longitudinal cross-sectional structure of the long-lasting and stable antibacterial coating on the surface of a titanium product prepared in Example 1. DETAILED DESCRIPTION

[0018] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0019] The method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product of the present invention comprises the following steps: pre-treating the titanium product and then performing anodizing to pre-implant copper elements, and finally performing four hydrothermal reactions to prepare gradient copper nanotubes. After cleaning and drying, the long-lasting and stable antibacterial coating on the surface of the titanium product can be obtained.

[0020] Follow the steps below to implement it: Step 1, pre-treatment of titanium products: The titanium product is polished in sequence using sandpaper from coarse to fine, and then the titanium product is pickled using a mixed solution to obtain a pre-treated titanium product; The mesh numbers of sandpaper from coarse to fine are 240 mesh, 400 mesh, 600 mesh, 800 mesh, 1200 mesh, and 2000 mesh; The mixed solution is prepared by mixing deionized water, nitric acid and hydrofluoric acid in a volume ratio of 12.5~10:2~4:0.5~1; Step 2, preparing titanium dioxide nanotubes pre-implanted with copper elements; The titanium product obtained in step 1 is anodized twice, and after the oxidation is completed, it is ultrasonically cleaned with deionized water and dried at room temperature to obtain titanium dioxide nanotubes pre-implanted with copper elements; During anodizing, the electrolyte is a mixture of ethylene glycol, water, ammonium fluoride, and copper chloride in a mass ratio of 96-90:2-5:1-2:1-3; The voltage of anodization is 50~60V and the time is 0.5~1h.

[0021] Step 3, subjecting the titanium dioxide nanotubes pre-implanted with copper obtained in step 2 to four hydrothermal reactions, washing and drying, to obtain a long-lasting and stable antibacterial coating on the surface of the titanium product; The specific steps are as follows: Step 3.1, mixing the titanium dioxide nanotubes pre-implanted with copper obtained in step 2 with the primary mixed solution, and performing a first hydrothermal reaction to obtain primary copper-doped nanotubes; The hydrothermal reaction temperature is 200~240℃, and the reaction time is 1~3h.

[0022] The primary mixed solution is formed by mixing barium hydroxide solution, copper chloride solution and sodium hydroxide solution; In the primary mixed solution, the volume ratio of barium hydroxide solution, copper chloride solution and sodium hydroxide solution is 1~2:1~2:96~98; The concentration of barium hydroxide solution is 0.01~0.03mol / L; the concentration of copper chloride solution is 0.005~0.02mol / L; the concentration of sodium hydroxide solution is 8~10mol / L; Step 3.2, mixing the primary copper-doped nanotubes obtained in step 3.1 with the secondary mixed solution, and performing a second hydrothermal reaction to obtain secondary copper-doped nanotubes; The hydrothermal reaction temperature is 200~240℃, and the reaction time is 1~3h.

[0023] The secondary mixed solution is formed by mixing barium hydroxide solution, copper chloride solution and sodium hydroxide solution; In the secondary mixed solution, the volume ratio of the barium hydroxide solution, the copper chloride solution and the sodium hydroxide solution is 1~2:3~4:94~96; The concentration of barium hydroxide solution is 0.01~0.03mol / L; the concentration of copper chloride solution is 0.03~0.05mol / L; the concentration of sodium hydroxide solution is 8~10mol / L; Step 3.3, mixing the secondary copper-doped nanotubes obtained in step 3.2 with the tertiary mixed solution, and performing a third hydrothermal reaction to obtain tertiary copper-doped nanotubes; The hydrothermal reaction temperature is 200~240℃, and the reaction time is 1~3h.

[0024] The tertiary mixed solution is a mixture of a barium hydroxide solution, a cupric chloride solution, and a sodium hydroxide solution; In the tertiary mixed solution, the volume ratio of barium hydroxide solution, copper chloride solution and sodium hydroxide solution is 1~2:5~6:92~94; The concentration of barium hydroxide solution is 0.01~0.03mol / L; the concentration of copper chloride solution is 0.06~0.08mol / L; the concentration of sodium hydroxide solution is 8~10mol / L; Step 3.4, mixing the tertiary copper-doped nanotubes obtained in step 3.3 with the quaternary mixed solution, performing a fourth hydrothermal reaction to obtain quaternary copper-doped nanotubes, washing and drying, and thus obtaining a long-lasting and stable antibacterial coating on the surface of the titanium product; The hydrothermal reaction temperature is 200~240℃, and the reaction time is 1~3h.

[0025] The fourth mixed solution is a mixture of a barium hydroxide solution, a cupric chloride solution and a sodium hydroxide solution; In the four mixed solutions, the volume ratio of barium hydroxide solution, copper chloride solution and sodium hydroxide solution is 1~2:7~8:90~92; The concentration of barium hydroxide solution is 0.01~0.03mol / L; the concentration of copper chloride solution is 0.1~0.12mol / L; the concentration of sodium hydroxide solution is 8~10mol / L.

[0026] Example 1 The method for preparing the long-lasting and stable antibacterial coating on the surface of titanium products of the present invention is specifically as follows: The titanium products were polished with 240, 400, 600, 800, 1200, and 2000 mesh sandpaper in turn; then pickled with 30 ml of a mixed solution of deionized water, nitric acid, and hydrofluoric acid (volume ratio of 10:4:1). Prepare 200 ml of a mixed solution of 1 wt.% ammonium fluoride, 1 wt.% copper chloride, 2 wt.% deionized water, and ethylene glycol. The treated titanium products were ultrasonically cleaned and dried with deionized water and used as anodes, and platinum sheets were used as cathodes, with a spacing of 20 mm between the two electrodes. The first anodization was performed at room temperature with a voltage of 60 V and a time of 1 h; then the second anodization was performed with a voltage of 60 V and a time of 30 min to obtain titanium dioxide nanotubes pre-implanted with copper elements. After the oxidation, the products were ultrasonically cleaned with deionized water and dried at room temperature. The titanium dioxide nanotubes pre-implanted with copper elements were subjected to the first hydrothermal reaction. 30 ml of deionized water was taken, 0.1539 g of barium hydroxide and 9.6 g of sodium hydroxide, and 0.0405 g of copper chloride were added to obtain a mixed solution T1. The container was a Teflon stainless steel autoclave, which was placed in an oven for heating. The temperature of the hydrothermal reaction was 200 ° C, and the time was 1.5 h. After washing and drying, the primary copper-doped titanium dioxide nanotube M1 was obtained. M1 was subjected to the second hydrothermal treatment, and the copper chloride content in the hydrothermal reaction solution T2 was increased to 0.162 g, and the other components remained unchanged. The temperature of the hydrothermal reaction was 200 ° C, and the time was 1.5 h. After washing and drying, the secondary copper-doped titanium dioxide nanotube M2 was obtained. M2 was subjected to the third hydrothermal treatment, and the copper chloride content in the hydrothermal reaction solution T3 was increased to 0.2835 g. The other components remained unchanged. The temperature of the hydrothermal reaction was 200 ° C, and the time was 1.5 h. After washing and drying, the tertiary copper-doped titanium dioxide nanotube M3 was obtained. M3 was subjected to the fourth hydrothermal treatment, and the copper chloride content in the hydrothermal reaction solution T4 was increased to 0.4455 g, while the other components remained unchanged. The temperature of the hydrothermal reaction was 200°C and the time was 1.5 h. After four hydrothermal reactions, gradient copper element nanotubes were prepared. After cleaning and drying, a long-lasting and stable antibacterial coating on the surface of titanium products could be obtained.

[0027] Example 2 The method for preparing the long-lasting and stable antibacterial coating on the surface of titanium products of the present invention is specifically as follows: The titanium products were polished with sandpaper of 240, 400, 600, 800, 1200, and 2000 mesh respectively; then pickled with 30ml of a mixed solution of deionized water, nitric acid, and hydrofluoric acid (volume ratio of 12.5:2:0.5). 200ml of a mixed solution of 2wt.% ammonium fluoride, 3wt.% copper chloride, 5wt.% deionized water, and ethylene glycol was prepared. The treated titanium products were ultrasonically cleaned with deionized water and dried as anodes, and platinum sheets were used as cathodes, with a spacing of 20mm between the two electrodes. The first anodization was carried out at room temperature with a voltage of 55V and a time of 1h; then the second anodization was carried out with a voltage of 55V and a time of 30min to obtain titanium dioxide nanotubes pre-implanted with copper elements. After the oxidation, the products were ultrasonically cleaned with deionized water and dried at room temperature. The titanium dioxide nanotubes pre-implanted with copper were subjected to the first hydrothermal treatment. 40 ml of deionized water was taken, 0.2052 g of barium hydroxide and 12.8 g of sodium hydroxide, and 0.027 g of copper chloride were added to obtain a mixed solution T1. The container was a Teflon stainless steel autoclave, which was placed in an oven for heating. The temperature of the hydrothermal reaction was 240 ° C, and the time was 1 h. After washing and drying, the primary copper-doped titanium dioxide nanotube M1 was obtained. M1 was subjected to the second hydrothermal treatment. The copper chloride content in the hydrothermal reaction solution T2 was increased to 0.162 g, and the other components remained unchanged. The temperature of the hydrothermal reaction was 240 ° C, and the time was 1 h. After washing and drying, the secondary copper-doped titanium dioxide nanotube M2 was obtained. M2 was subjected to the third hydrothermal treatment. The copper chloride content in the hydrothermal reaction solution T3 was increased to 0.324 g, and the other components remained unchanged. The temperature of the hydrothermal reaction was 240 ° C, and the time was 1 h. After washing and drying, the tertiary copper-doped titanium dioxide nanotube M3 was obtained. M3 was subjected to the fourth hydrothermal treatment, and the copper chloride content in the hydrothermal reaction solution T4 was increased to 0.54 g, while the other components remained unchanged. The temperature of the hydrothermal reaction was 240°C and the time was 1 h. After four hydrothermal reactions, gradient copper nanotubes were prepared. After cleaning and drying, a long-lasting and stable antibacterial coating on the surface of titanium products could be obtained.

[0028] Example 3 The method for preparing the long-lasting and stable antibacterial coating on the surface of titanium products of the present invention is specifically as follows: The titanium products were polished with sandpaper of 240, 400, 600, 800, 1200, and 2000 mesh respectively; then pickled with 30ml of a mixed solution of deionized water, nitric acid, and hydrofluoric acid (volume ratio of 10:4:1). Prepare 200ml of a mixed solution of 1.5wt.% ammonium fluoride, 2wt.% copper chloride, 3wt.% deionized water, and ethylene glycol. The treated titanium products were ultrasonically cleaned and dried with deionized water and used as anodes, and platinum sheets were used as cathodes, with a spacing of 20mm between the two electrodes. The first anodization was performed at room temperature with a voltage of 50V and a time of 1h; then the second anodization was performed with a voltage of 50V and a time of 30min to obtain titanium dioxide nanotubes pre-implanted with copper elements. After the oxidation, the products were ultrasonically cleaned with deionized water and dried at room temperature. The titanium dioxide nanotubes pre-implanted with copper elements were subjected to the first hydrothermal treatment. 35 ml of deionized water was taken, 0.1796 g of barium hydroxide and 11.2 g of sodium hydroxide, and 0.0709 g of copper chloride were added to obtain a mixed solution T1. The container was a Teflon stainless steel autoclave, which was placed in an oven for heating. The temperature of the hydrothermal reaction was 220 ° C, and the time was 3 hours. After washing and drying, the primary copper-doped titanium dioxide nanotube M1 was obtained. M1 was subjected to the second hydrothermal treatment, and the copper chloride content in the hydrothermal reaction solution T2 was increased to 0.2126 g, and the other components remained unchanged. The temperature of the hydrothermal reaction was 220 ° C, and the time was 3 hours. After washing and drying, the secondary copper-doped titanium dioxide nanotube M2 was obtained. M2 was subjected to the third hydrothermal treatment, and the copper chloride content in the hydrothermal reaction solution T3 was increased to 0.3544 g. The other components remained unchanged. The temperature of the hydrothermal reaction was 220 ° C, and the time was 3 hours. After washing and drying, the tertiary copper-doped titanium dioxide nanotube M3 was obtained. M3 was subjected to the fourth hydrothermal treatment, and the copper chloride content in the hydrothermal reaction solution T4 was increased to 0.5434 g, while the other components remained unchanged. The temperature of the hydrothermal reaction was 220°C and the time was 3 h. After four hydrothermal reactions, gradient copper nanotubes were prepared. After cleaning and drying, a long-lasting and stable antibacterial coating on the surface of titanium products could be obtained.

[0029] Example 4 The method for preparing the long-lasting and stable antibacterial coating on the surface of titanium products of the present invention is specifically as follows: The titanium products were polished with sandpaper of 240, 400, 600, 800, 1200, and 2000 mesh respectively; then pickled with 30ml of a mixed solution of deionized water, nitric acid, and hydrofluoric acid (volume ratio of 10:4:1). Prepare 200ml of a mixed solution of 1wt.% ammonium fluoride, 3wt.% copper chloride, 4wt.% deionized water, and ethylene glycol. The treated titanium products were ultrasonically cleaned and dried with deionized water and used as anodes, and platinum sheets were used as cathodes, with a spacing of 20mm between the two electrodes. The first anodization was performed at room temperature with a voltage of 60V and a time of 1h; then the second anodization was performed with a voltage of 60V and a time of 30min to obtain titanium dioxide nanotubes pre-implanted with copper elements. After the oxidation, the products were ultrasonically cleaned with deionized water and dried at room temperature. The titanium dioxide nanotubes pre-implanted with copper elements were subjected to the first hydrothermal treatment. 25 ml of deionized water was taken, 0.1283 g of barium hydroxide and 8 g of sodium hydroxide, and 0.0675 g of copper chloride were added to obtain a mixed solution T1. The container was a Teflon stainless steel autoclave, which was placed in an oven for heating. The temperature of the hydrothermal reaction was 230 ° C, and the time was 2.5 h. After washing and drying, the primary copper-doped titanium dioxide nanotube M1 was obtained. M1 was subjected to the second hydrothermal treatment, and the copper chloride content in the hydrothermal reaction solution T2 was increased to 0.1688 g, and the other components remained unchanged. The temperature of the hydrothermal reaction was 230 ° C, and the time was 2.5 h. After washing and drying, the secondary copper-doped titanium dioxide nanotube M2 was obtained. M2 was subjected to the third hydrothermal treatment, and the copper chloride content in the hydrothermal reaction solution T3 was increased to 0.27 g. The other components remained unchanged. The temperature of the hydrothermal reaction was 230 ° C, and the time was 2.5 h. After washing and drying, the tertiary copper-doped titanium dioxide nanotube M3 was obtained. M3 was subjected to the fourth hydrothermal treatment, and the copper chloride content in the hydrothermal reaction solution T4 was increased to 0.405 g, while the other components remained unchanged. The temperature of the hydrothermal reaction was 230°C and the time was 2.5 h. After four hydrothermal reactions, gradient copper nanotubes were prepared. After ultrasonic cleaning with deionized water, ethanol and acetone and drying, a long-lasting and stable antibacterial coating on the surface of titanium products was obtained.

[0030] Example 5 The method of the present invention prepares gradient copper nanotubes by pre-implanting copper elements through anodic oxidation and four hydrothermal reactions, thereby obtaining a titanium product surface coating with excellent antibacterial performance, long-lasting antibacterial effect, and stable release of antibacterial agents; taking the titanium product antibacterial material prepared in Example 1 as an example, Figure 1 This is a schematic diagram of the cross-sectional structure of a copper-doped titanium product prepared by anodization and four hydrothermal reactions. It can be seen from the figure that the surface of the titanium product is a nanoscale tubular structure, barium titanate is evenly distributed, and the content of copper titanate gradually increases from the inside to the outside. This structure not only ensures the antibacterial properties of the titanium product, but also ensures the long-term and stable release of the antibacterial agent on the surface of the titanium product.

[0031] Example 6 The antibacterial rates of the long-acting stable antibacterial coatings on the surfaces of titanium products prepared in Examples 1, 2, 3 and 4 of the present invention and the copper ion release amounts at various time points are shown in Table 1.

[0032] Table 1 Antibacterial rate of coatings in various embodiments and daily release of copper ions at various time points

[0033] The present invention prepares gradient copper nanotubes by pre-implanting copper anodic oxidation and four hydrothermal reactions, and obtains a long-lasting and stable antibacterial coating on the surface of titanium products. It can be seen from the above table that the antibacterial rates of the antibacterial coatings on the surface of titanium products prepared in Examples 1, 2, 3 and 4 are 99.97%, 99.99%, 99.98% and 99.99%, respectively, with excellent antibacterial effects; the copper ion release on the 90th day is 1.20 mg·L -1 、1.08 mg·L -1 , 1.14 mg·L -1 , 1.19 mg·L -1 The release amount of copper ions in the first 90 days hardly changes. The long-lasting and stable antibacterial coating on the surface of titanium products of the present invention has good application prospects.

[0034] The method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product of the present invention prepares a gradient copper nanotube by pre-implanting copper elements through anodic oxidation and four hydrothermal reactions, and dopes copper ions into the surface of the titanium product to obtain a long-lasting and stable antibacterial coating on the surface of the titanium product. The preparation method of the present invention obtains a titanium product surface coating with excellent antibacterial performance, long-lasting antibacterial effect, and stable copper ion release, solving the problem that titanium products have no antibacterial properties, and that the existing antibacterial metal-doped titanium alloys have a short antibacterial effect duration and unstable metal particle release.

Claims

1. A method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product, characterized in that: Follow the steps below to implement it: Step 1, pretreatment of titanium products; Step 2, anodizing the titanium product obtained in step 1 twice, ultrasonically cleaning it with deionized water after the oxidation is completed, and drying it at room temperature to obtain titanium dioxide nanotubes pre-implanted with copper elements; Step 3, subjecting the titanium dioxide nanotubes pre-implanted with copper obtained in step 2 to four hydrothermal reactions, washing and drying, to obtain a long-lasting and stable antibacterial coating on the surface of the titanium product.

2. The method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product according to claim 1, characterized in that: In the step 1, specifically: The titanium product is polished in sequence using sandpaper from coarse to fine, and then pickled using a mixed solution to obtain a pre-treated titanium product.

3. The method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product according to claim 2, characterized in that: The mixed solution is prepared by mixing deionized water, nitric acid and hydrofluoric acid in a volume ratio of 12.5~10:2~4:0.5~1.

4. The method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product according to claim 1, characterized in that: In the step 2, during anodization, the electrolyte is a mixture of ethylene glycol, water, ammonium fluoride, and copper chloride in a mass ratio of 96-90:2-5:1-2:1-3; the anodization voltage is 50-60V, and the time is 0.5-1h.

5. The method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product according to claim 1, characterized in that: In step 3, the specific steps are as follows: Step 3.1, mixing the titanium dioxide nanotubes pre-implanted with copper obtained in step 2 with the primary mixed solution, and performing a first hydrothermal reaction to obtain primary copper-doped nanotubes; Step 3.2, mixing the primary copper-doped nanotubes obtained in step 3.1 with the secondary mixed solution, and performing a second hydrothermal reaction to obtain secondary copper-doped nanotubes; Step 3.3, mixing the secondary copper-doped nanotubes obtained in step 3.2 with the tertiary mixed solution, and performing a third hydrothermal reaction to obtain tertiary copper-doped nanotubes; Step 3.4, mixing the tertiary copper-doped nanotubes obtained in step 3.3 with the quaternary mixed solution, performing a fourth hydrothermal reaction to obtain quaternary copper-doped nanotubes, washing and drying, and thus obtaining a long-lasting and stable antibacterial coating on the surface of the titanium product.

6. The method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product according to claim 5, characterized in that: The temperatures of the four hydrothermal reactions were all 200~240℃, and the reaction times were all 1~3h.

7. The method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product according to claim 5, characterized in that: The primary mixed solution, the secondary mixed solution, the tertiary mixed solution and the quaternary mixed solution are all prepared by mixing barium hydroxide solution, copper chloride solution and sodium hydroxide solution; In the primary mixed solution, the volume ratio of the barium hydroxide solution, the copper chloride solution and the sodium hydroxide solution is 1-2:1-2:96-98; the concentration of the barium hydroxide solution is 0.01-0.03 mol / L; the concentration of the copper chloride solution is 0.005-0.02 mol / L; the concentration of the sodium hydroxide solution is 8-10 mol / L; In the secondary mixed solution, the volume ratio of the barium hydroxide solution, the copper chloride solution and the sodium hydroxide solution is 1-2:3-4:94-96; the concentration of the barium hydroxide solution is 0.01-0.03 mol / L; the concentration of the copper chloride solution is 0.03-0.05 mol / L; the concentration of the sodium hydroxide solution is 8-10 mol / L; In the three mixed solutions, the volume ratio of barium hydroxide solution, copper chloride solution and sodium hydroxide solution is 1~2:5~6:92~94; the concentration of barium hydroxide solution is 0.01~0.03mol / L; the concentration of copper chloride solution is 0.06~0.08mol / L; the concentration of sodium hydroxide solution is 8~10mol / L; In the four mixed solutions, the volume ratio of the barium hydroxide solution, the copper chloride solution and the sodium hydroxide solution is 1~2:7~8:90~92; the concentration of the barium hydroxide solution is 0.01~0.03mol / L; the concentration of the copper chloride solution is 0.1~0.12mol / L; and the concentration of the sodium hydroxide solution is 8~10mol / L.

8. The antibacterial coating prepared by the method for preparing a long-lasting and stable antibacterial coating on the surface of a titanium product as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation and silver doping methods of titania nanotubes

    CN103820834A

  • Metal particle reinforced titanium dioxide antibacterial compound

    CN112219867A

  • Metal ion doped titanium dioxide nano coating, preparation method and application of metal ion doped titanium dioxide nano coating in nerve and bone tissue repair

    CN115444980A

  • Preparation method of silver-containing nano-composite antibacterial coating

    CN115478255A

Cited By

  • Copper-doped titanium-based energy-storage antibacterial material as well as preparation method and application thereof

    CN120738726A